The relationship between three subtypes of safety behaviors and social anxiety: Serial mediating effects of state and trait post-event processing - Kim, Dahye; Kang, Ha-Yeon; Ahn, Jung-Kwang (Frontiers in Psychology, 2022)
The cognitive model for social anxiety disorder (SAD) highlights the role of safety behaviors and post-event processing (PEP). We identify the serial mediating effect of state and trait PEP between three types of safety behaviors (impression management, avoidance behavior, and anxiety-symptom control) and social anxiety. Given that the associations between the three subtypes of safety behaviors and two perspectives of PEP have not yet been examined, we aimed to investigate these relationships according to the level of social anxiety. A total of 487 participants participated in an online survey. Participants were classified into two groups based on their social anxiety scores: high and low social anxiety groups. We used Social Behavior Questionnaire to distinguish three types of safety behaviors and the State and Trait versions of the Post-Event Processing Inventory to identify two perspectives of PEP. We used descriptive statistics and an independent t-test to compare the high and low social anxiety groups. Mediation effects were examined using mediation analysis and bootstrapping with 5,000 replications. The results showed that the three safety behaviors had different effects on social anxiety via PEP. In the high social anxiety group, avoidance behavior and anxiety-symptom control predicted social anxiety positively, whereas impression management did not. However, with state PEP and trait PEP as mediators, impression management and avoidance behavior positively predicted social anxiety but not anxiety-symptom control. In the low social anxiety group, only avoidance behavior was significantly related to social anxiety, but when the state and trait PEP were mediated, the effect disappeared. These results indicated that impression management could affect social anxiety only mediated by PEP in people with social anxiety. A better understanding of the content and processes underpinning safety behavior and PEPs might have important implications for the prevention and treatment of social anxiety disorder.